Symposium 2: DIGIFLEX - from flexible and digital courses to an overall networked learning perspective on digital course design - Lundgren, Lena; Ottestig, Ann (Proceedings of the International Conference on Networked Learning, 2024)
The digital two-way communication that society expects today can be said to blur the boundaries between the universities and the surrounding society. As the campus becomes more of an open network, the gap between formal and informal learning narrows. One can see a shift towards a perspective of lifelong learning with a more social and global perspective. Seen in that perspective, higher education has a greater value for people, than just specific skills or a specific degree. How people in society interact with various groups and organizations on social media also demonstrates this development and it challenges how we traditionally view learning. It also affects how the university conducts course design. Students and educators have come to expect the use of new digital tools. Many of these tools contribute to interaction between educators and students in collaborative learning. In a societal perspective we see a two-way exchange of meanings and needs, which makes it possible to create solutions that neither the university nor organizations in society could have adopted on their own. The focus of this paper is the course design process of a commissioned education course, DIGIFLEX. The practice meanings from students, colleagues and a reference group are referred to as feedback loops. These feedback loops continuously drove the course design and development forward and clearly indicated the need for an adaption to a more societal context. The design process is described via three stages and two feedback loops. The first stage focused on finding a modern digital design with lots of audiovisual elements for short and flexible courses. In the first feedback loop, we gained inspiration via a learning technology conference, which led to sessions with reverse brainstorming where the project group further challenged the standard norm for course design. In step two, the pilot course was implemented with the new elements generated from the first feedback loop. We received support from a reference group with expertise in networked learning and the students evaluated the course. Our findings show a need for more dialogue and informal structure as complement to the existing digital course design. This insight was confirmed by the experiences and lessons learned from distance education during the pandemic. There is a need for a networked learning perspective in this kind of digital course design. More frequent reconciliations, evaluations of needs and expectations from the surrounding society is important for the success of similar projects in the future.